Methodology for stakeholder-led identification of platforms for healthier diets (mechanisms to support the scaling and anchoring of food systems transformation for healthier diets) in Bangladesh, Ethiopia, Nigeria, and Viet Nam - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The methodology and report from four countries was published in 2021. A synthesis paper was published in Global Food Security. The methodology was used to draft the next phase of a multilateral project called Drivers of Food Choice, which unfortunately is on hold due to the funders' own financial circumstances.